Work Life Balance of Couple Deped Teachers in the New Normal: A Phe-nomenological Study - Delavin, Elreen Aguilar; Dumaguin, Ian Mark L. (Future Science / FSH-PH Publications, 2022)
The purpose of this study is to determine varied responses on socio-demographic profile of couple DepEd teachers in the new normal in terms of age, highest educational attainment, school attainment, position, school designation, salary grade level, take-home pay, years in service, number of children, years of being married, family size and another source of income, exploring different lived experiences of couple DepEd teachers along childcare/dependent care, support from family, self – management, life expectations, life satisfactions, workplace support, workload, financial management, work expectations and work satisfactions and recommend a policy framework that can be suggested in responding to the work life balance of couple DepEd teachers in the new normal. This research is focused on the Province of Masbate, specifically in the municipality of Mandaon. Five couple teachers who are teaching in public schools were pre – selected. The study employed qualitative method of research, specifically phenomenological analysis to gather the lived experiences of five couple DepEd teachers. A descriptive phenomenological approach to inquiry revealed that socio-demographic profile of couple DepEd teachers in the new normal is varied but related with each other in terms of age, educational attainment, position, designation, salary grade level, take-home pay, years in the service, and years of being married. Lived experiences of couple DepEd teachers in the new standard can be divided into work (workplace support, workload, financial management, and work expectations) and life (childcare, support from family, self–management, life expectations, life satisfaction, and financial management). Work and life experiences are factors that affect the work life balance of couple DepEd teachers. The researcher recommends a policy rooted on work and life satisfaction which are needed as measures for a right work life balance in the new normal.